2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00513
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion Aware Unsupervised Learning of Optical Flow

Abstract: It has been recently shown that a convolutional neural network can learn optical flow estimation with unsupervised learning. However, the performance of the unsupervised methods still has a relatively large gap compared to its supervised counterpart. Occlusion and large motion are some of the major factors that limit the current unsupervised learning of optical flow methods. In this work we introduce a new method which models occlusion explicitly and a new warping way that facilitates the learning of large mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
292
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(301 citation statements)
references
References 55 publications
(78 reference statements)
1
292
0
Order By: Relevance
“…Smoothness Loss. For the smoothness loss L sm , we adopt the formulation introduced in [25] which encourages the correspondence maps to be locally smooth but also maintains edges that should be aligned with the structure of images:…”
Section: Unsupervised Loss Functionsmentioning
confidence: 99%
“…Smoothness Loss. For the smoothness loss L sm , we adopt the formulation introduced in [25] which encourages the correspondence maps to be locally smooth but also maintains edges that should be aligned with the structure of images:…”
Section: Unsupervised Loss Functionsmentioning
confidence: 99%
“…We use a grid search to set the balance parameters, λ D , λ O and λ, to 0.1, 0.1 and 0.05, respectively. We follow the experimental setting in [12], [16], [49], [60] to set other parameters, and fix them in all experiment: α = 0.5, β = 0.85, γ = 10, and = 1. We compute optical flow using the DIS-Flow method [61] that offers a good compromise in terms of runtime and accuracy.…”
Section: A Trainingmentioning
confidence: 99%
“…We found that a photoconsistency loss on the reblurred images alone is insufficient to constrain the optical flow. We thus add an additional self-supervised photometric loss on the optical flow as proposed in prior work [12], [20], [34] and detailed in Section III-D. The input to this loss function is a Note that bilinear interpolation cannot be applied since the warped grid might not be rectangular due to the non-uniform optical flow, as shown in Fig.…”
Section: Image Warpingmentioning
confidence: 99%